(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
The reforms and creative work being carried out in our country serve the well-being of the population. Improvement and greening work are being carried out. Practical work in this regard is also being carried out in the Shorchi district of the Surkhandarya region of the Republic of Uzbekistan. In particular, as part of the national project “Green Space”, which is a very important and consistent with our values, the call of the head of state is to plant seedlings. There is a joke that a shepherd’s staff forgotten in the plow takes root by spring. In fact, this is not a simple story. This is an expression of the richness of our soil and its harmony with the ground.